The Guide to the Federal Budget: Fiscal 1998 - Collender, Stanley E. (Rowman & Littlefield Publishers, 1997)
Rowman & Littlefield is proud to publish the 17th edition of what is now considered to be the most useful reference book available on the federal budget. In The Guide to the Federal Budget, Fiscal 1998, Stanley E. Collender, among a handful of people who have worked for both the House and Senate budget committees, analyzes the extensive debates surrounding the fiscal 1997 budget and explains in detail such 1998 budget challenges as the line item veto, entitlement spending, and the persistent politics of divided government. An indispensable guide for policy analysts, The Guide to the Federal Government, Fiscal 1998 is written at a level accessible to general readers and includes illuminating appendices, a revised and updated glossary of key terms, and a thorough index. With a concluding chapter entitled "How to Read and Use the Federal Budget," and a new chapter on the line item veto, this book will be particularly useful for courses in Budget Politics and Analysis and Public Policy.